2020
DOI: 10.1002/mde.3110
|View full text |Cite
|
Sign up to set email alerts
|

Indirect taxation with shadow cost of public funds in mixed oligopoly

Abstract: We adopt a mixed oligopoly model, where a state‐owned welfare‐maximizing public firm competes with a profit‐maximizing private firm, to compare the welfare effects of the specific and ad valorem tax in the presence of the shadow cost of public funds. Following the assumption of most previous literature that total output is constant under specific and ad valorem taxation, we find that, when the shadow cost of public funds exists, the tax policy must be adjusted according to the privatization level of the public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The main purpose of this paper is to analyze the impacts of β and e on equilibrium outcomes under different competition modes. Therefore, we assume that the product is homogeneous, which is an assumption adopted by many scholars (Lee & Wang, 2018;Xu & Lee, 2019;Zhang et al, 2020). In future research, we will focus on the analysis of product differentiation.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…The main purpose of this paper is to analyze the impacts of β and e on equilibrium outcomes under different competition modes. Therefore, we assume that the product is homogeneous, which is an assumption adopted by many scholars (Lee & Wang, 2018;Xu & Lee, 2019;Zhang et al, 2020). In future research, we will focus on the analysis of product differentiation.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…(2019), and Zhang et al. (2020) compared an ad valorem tax and a specific tax in a closed economy. Of note, Mujumdar and Pal (1998) and Tao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the shadow cost of public funds, Zhang et al. (2020) reported that if the privatization level is low (medium, high), the government must adopt ad valorem (specific, ad valorem) tax.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations